2000
DOI: 10.1044/0161-1461.3102.116
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Examiner's Race on the Performance of African American Children on the SCAN

Abstract: Although examiner race did not appear to influence SCAN performance for this group of children, the possibility of a race effect needs further investigation with a larger sample, as does the clinical utility of the SCAN as a processing-dependent measure. The significant learning effect also suggests potential problems with the test-retest reliability of the SCAN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Previous studies have investigated examiner bias due to gender in oral exams. 2,3 Research focused on oral exams using a single examiner report mixed results related to gender bias, whereas studies focused on oral exams using pairs of examiners have found evidence of gender bias. [4][5][6][7][8][9] In one study, male/male examiner pairs rated female examinees significantly higher than male examinees compared to other combinations of examiner gender pairs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated examiner bias due to gender in oral exams. 2,3 Research focused on oral exams using a single examiner report mixed results related to gender bias, whereas studies focused on oral exams using pairs of examiners have found evidence of gender bias. [4][5][6][7][8][9] In one study, male/male examiner pairs rated female examinees significantly higher than male examinees compared to other combinations of examiner gender pairs.…”
Section: Introductionmentioning
confidence: 99%
“…These warrant caution as they are not universally accepted and have suspect or confirmed flaws. The construct validity, reliability, and actual sustained calibration have been questioned (Smith, Bradham, Chandler, & Wells, 2000; Woods, Pena, & Martin, 2004). Rather than relying on specific equipment-mediated testing, surveys and questionnaires have also been used.…”
Section: Auditory Testingmentioning
confidence: 99%
“…They must receive adequate education, with multicultural awareness, in order to build knowledge of a variety of culturally appropriate techniques (5,6) . Hence, culturally competent SLPs should be aware of their own values and biases and be sensible to the values and needs of individuals with diverse backgrounds (7) . SLPs must develop a thoughtful and sensitive attitude about cultural background because there are no established solutions for dealing with every situation involving a diverse caseload (8) .…”
Section: Introductionmentioning
confidence: 99%